Strategi Penerapan Teknik Zigzag sebagai Solusi Terbaik dalam Pengeritingan Rambut Modern - Indah Regina; Ridha Alya Putri; Cut Yasmine Suffia Dara; Siti Fazira M (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
The hair beauty industry continues to develop along with the increasing public demand for an aesthetic, modern appearance, and in line with developing trends. One innovation in the field of hair styling is the zigzag pattern hair curling technique that offers more natural, voluminous, and dynamic curling results compared to conventional techniques. This study aims to analyze the strategy of implementing the zigzag technique as an innovation in modern hair curling through a literature study approach. The research method used is qualitative with a literature review research type. Data were obtained through searching various relevant scientific sources, such as national and international journals, scientific articles, and reference books that discuss modern hair curling techniques, hair styling innovations, and hair health. Literature searches were conducted through Google Scholar, GARUDA, and ScienceDirect using keywords that are appropriate to the research topic. Data analysis was carried out through the stages of data reduction, grouping findings, synthesizing information, and drawing descriptive conclusions. The results of the study indicate that the zigzag technique has advantages in producing a more natural, flexible, and voluminous hair appearance compared to conventional curling techniques. Furthermore, this technique has the potential to increase the durability of curls and minimize the risk of hair damage when applied with proper procedures and the use of appropriate hair protection products. The success of the zigzag technique is influenced by the competence of the hairstylist, the use of adequate tools, the selection of hair care products, and an effective service promotion strategy. Therefore, the zigzag technique can be seen as a relevant innovation in the development of modern salon services and beauty education.